Seismic activity on the territory of Slovakia in 2016 - KYSEL, Róbert; CIPCIAR, Andrej; CHOVANOVÁ, Zuzana; CSICSAY, Kristián; FOJTÍKOVÁ, Lucia; GÁLIS, Martin; KRISTEKOVÁ, Miriam (Contributions to Geophysics and Geodesy, 2019)
The National Network of Seismic Stations of Slovakia (NNSS) consists of eight short period and five broadband permanent seismic stations and a data centre located at the Earth Science Institute of the Slovak Academy of Sciences (ESI SAS). The NNSS recorded and detected 10888 seismic events from all epicentral distances in 2016. Totally 87 earthquakes originated in the territory of Slovakia in 2016. This paper provides basic information on the configuration of the NNSS, routine data processing, seismic activity on the territory of Slovakia in 2016 as well as macroseismic observations collected in 2016.